The Effect of Air Pollution on the Occurrence of Nonspecific Conjunctivitis - Zhiwei Li; Xiaoyan Bian; Jianguang Yin; Xiaoli Zhang; Guoying Mu (Journal of Ophthalmology)
Purpose. To investigate the short-term effect of air pollution on occurrence of nonspecific conjunctivitis. Methods. Data were collected from outpatient visits from cases with conjunctivitis over a period of one year. Regression analysis was performed to evaluate the relationship between the number of outpatient visits and the air quality and the lag effect of air quality on conjunctivitis occurrence. Results. The air quality index on the day of presentation (P=0.023), one day before presentation (P=0.049), and two days before presentation day (P=0.050) had a positive relation with outpatient visits for conjunctivitis. The air quality index (P=0.001) and outpatient visits number per day (P=0.013) in autumn and winter (October to March) were significantly higher than those in spring (April) and summer (September). Conclusions. The air quality index within two days before presentation affected the probability of attending the outpatient clinic for nonspecific conjunctivitis. High number of cases can be expected in colder season.